Air bearing surface design for high flying stabilities - Lim, Choon Ming. (2009)
With continuous technology improvement and the demand for higher recording density towards tera-bit per square inch and more, the flying height of the slider must be reduced greatly to the region of nanometre scale. At such an ultralow flying height, there is a possibility for magnetic head-platter disk crashes or instable head-disk spacing due to short-range interaction forces. Therefore, designing an Air Bearing Surface (ABS) that provides good flying stability properties with the capability of following the disk vibration and/or disk waviness during operation is very important in today context. The purpose of the Air Bearing Surface (ABS) is to create an air cushion to allow the slider to fly over the platter disk at extreme low height without any physical contact. In this project, the in-house software ABSolution self-developed by the Spintronics, Media & Interface Division of the Data Storage Institute (DSI), Singapore is used for the designing of a suitable ABS. Basic understanding of the hard disk drive mechanism is explained in this report. In addition, research on the internet, reference books and published journals are used to summarize various way of improving the flying height stability. Three different ABS sliders have been designed for this final year project. Each design undergoes 2 static and 2 dynamic simulations using the ABSolution. Three different lubrication models are also briefly discussed and are used in the static and dynamic simulations. The results obtained are tabulated and discussed. It is observed that in such nano-scale spaces, intermolecular and electrostatic interactions cannot be neglected. In addition, the forces responsible for the ABS flight are examined and discussed. One ABS design is considered to be the better design out of the three created and the reason is explained.